1998
DOI: 10.1023/a:1018790003416
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Research on worry during the past 15 years has revealed a remarkable amount of knowledge about this pervasive human phenomenon. Worry involves a predominance of verbal thought activity, functions as a type of cognitive avoidance, and inhibits emotional processing. Worry also produces not only anxious experience but depressive affect as well. Recent evidence suggests that the very private experience of worry is developmentally connected to enmeshed childhood relationships with the primary caregiver and is curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
214
2
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 670 publications
(237 citation statements)
references
References 51 publications
14
214
2
7
Order By: Relevance
“…[10]) suggests that the core symptom of GAD, uncontrollable worry, allows patients to cognitively avoid otherwise emotionally disturbing issues and perceived dangers. From this point of view, worry is a predominantly cognitive-verbal activity that inhibits full emotional processing.…”
Section: Introductionmentioning
confidence: 99%
“…[10]) suggests that the core symptom of GAD, uncontrollable worry, allows patients to cognitively avoid otherwise emotionally disturbing issues and perceived dangers. From this point of view, worry is a predominantly cognitive-verbal activity that inhibits full emotional processing.…”
Section: Introductionmentioning
confidence: 99%
“…By using a mental imagery paradigm, Schienle et al [34] found that after viewing images eliciting emotions of disgust female participants scoring high on disgust sensitivity displayed lower activation in the amygdalae. These authors suggest that this reduced response pattern reflects cognitive avoidance, which helps to control somatic arousal (see also [6]). Avoidance strategies to regulate emotional stress responses, while viewing aversive stimuli, have been reported in particular in 'anxious' subjects [33].…”
mentioning
confidence: 98%
“…In particular, considering previous work on the role of visual images 1 It should be noted that EmoFT is conceived here as a broad phenomenon that include any type of future-oriented thought that is accompanied by an emotion. Therefore, this notion could potentially include more specific types of future-oriented thoughts that have been previously described in the literature, such as worries (which predominantly involve verbal thoughts about negative events that we are afraid might happen in the future; Borkovec, Ray, & Stober, 1998).…”
mentioning
confidence: 99%